Assessment of endometrial integrin beta 5 in women with unexplained recurrent pregnancy loss - Ahmed Mohamed Fathy; Ahmed Youssef Rizk; Nahla Abd El Azeez Nosair; Ahmed Mohamed Abdelkarim; Mostafa Farag Ellakany (Journal of the Pakistan Medical Association, 2023)
N/A